Relocalización de los sistemas de producción agro-alimentaria en la Union Europea - Ilbery, Brian (Geographicalia, 2016)
Despite globalising tendencies in food supply systems, there is a movement towards the relocalisation of food production and consumption. Such a movement relates to a range of factors and this paper examines attempts to encourage the relocalisation of food supply systems at international (EU) and national (UK) scales. Case studies of PDOs/PGIs and regional food groups show that efforts to link 'product to place' have, so far, had relatively little impact on local economic development, especially in those rural aseas marginalised by agricultural restructuring processes. More research is needed on the relocalisationof food supply systems, in relation to such concepts as social embeddedness, quality and certification, and endogenous rural development.
Keywords: Agrarian Geography; Relocalisation; Protected Designation of Origin /Protected Geographical Indication; European Union; United Kingdom